Molecular interactions of Toxoplasma gondii dense granule 23 (GRA23) with host proteins PEX3 and TRAP1 - Fan, Xuewei; Zhang, Nan; Zhang, Xichen; Li, Shudong; Fu, Jiangming; Sun, Min; Ma, Xiaoxiao; Khan, Muhammad Zahoor; Jiang, Xin (Frontiers in Veterinary Science, 2025)
BackgroundToxoplasma gondii, an obligate intracellular protozoan, utilizes dense granule proteins to modulate host cell processes. Dense granule protein 23 (GRA23) facilitates molecular trafficking between the parasitophorous vacuole and host cell cyto-plasm, though its specific host protein interactions remain poorly characterized.MethodsThis study employed pull-down assays coupled with mass spectrometry to identify host proteins interacting with GRA23.ResultsAmong 35 proteins identified, peroxisomal biogenesis factor 3 (PEX3) and TNF receptor-associated protein 1 (TRAP1) were validated through bimolecular fluorescence complementation (BiFC) and co-immunoprecipitation (Co-IP) assays. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses revealed significant enrichment of these interacting proteins in metabolic pathways and cellular processes related to reproduction, growth, and development.ConclusionThe interaction between GRA23 and PEX3 suggests potential parasite modulation of peroxisomal functions, while its association with TRAP1 indicates possible exploitation of host chaperone mechanisms. This study provides the first evidence that GRA23 interacts with host proteins implicated in key cellular functions, offering novel insights into T. gondii pathogenesis and potential therapeutic targets for toxoplasmosis treatment.